“The use of interactive teaching strategies in teacher education: lessons from the Teaching Internship Discipline - Carolino, G. S.; Silva, Maria G.V.; Sousa, A. (Porto ICRE’24 - 4th Porto International Conference on Research in Education, 2024)
The present paper aims to present the methodological components of the academic extension project entitled "Workshop on Active Methodologies and Digital Technologies," carried out as part of the Teaching Internship Discipline of the Doctorate Course in Teaching of the Northeastern Education Network (RENOEN/UFC). According to Joaquim and Camargo (2020, p. 1), "the practice of workshops in the field of education can reveal itself as a fruitful instrument for the production of knowledge, processes of subjunctivization, and emancipation." This investigation focused primarily on the participants' perspective, emphasizing their perceptions of the effectiveness of the methodologies applied in training and the structural methodological elements of the project. The methodological itinerary of this extension action was guided by applied bibliographic research and thematic deepening, adopting a theoretical-practical approach. As a means of data collection, a questionnaire was used, and applied to the course participants, allowing the evaluation of various aspects of the methods employed and the level of satisfaction in their application. The training was face-to-face, with online methodological components, and involved the participation of the discipline coordinator, 9 (nine) doctoral teacher-researchers, and 12 (twelve) students majoring in science education. The main purpose of the training was to promote dynamic learning environments, encouraging future teachers to become acquainted with active methodologies and digital languages. The aim was for them to use Information and Communication Digital Technologies (ICDT) critically, interdisciplinarity, meaningfully, and ethically. The workshop was divided into 4 (four) didactic units: i) active methodologies with an emphasis on problem-based learning (PBL/ABP); ii) paths for curating digital learning objects (DLOs); iii) active learning with the support of digital technologies in Science teaching; and iv) active learning with an educational proposal in the Maker culture. During the execution of the units, interactive pedagogical models and digital tools were explored for the creation of games and innovative educational strategies. Corroborating with this strategy, Sanches (2021) states that the authoring of games, in formative moments aimed at teachers, becomes a powerful tool through which a closer dialogue is established between the author and their object of study. To monitor and promote greater interactivity among participants, the workshop used Virtual Learning Environments (VLEs) and software from different applications, such as organization of units, repository of scientific materials, conducting online activities, and exchange of experiences among all participants. After the analysis of the questionnaire, it was observed that the majority of the course participants were satisfied with the methodology, clarity, practical experience, use of technological resources, interactivity, coherence, and applicability of the contents and methods of the workshop, thus confirming the relevance of implementing this strategy in Science education through the didactic-methodological resources presented.